Development Towards A Preliminary ‘Risk Prediction Hazard Model’ For Nosocomial Infection In Adult Intensive Care Units In Malaysia - Katherason, Supaletchimi Gopal (2010)

(untitled)
Device-associated nosocomial infection (NI) increases the mortality and morbidity rate (>30%) and healthcare costs. Studies on NI were limited in Malaysia. Most studies were retrospective or on point prevalence. Gap in Knowledge (K), Attitude (A), Practice (P) studies on prevention of ICU-acquired NIs were not available in Malaysia. The objectives of the study were to (i) identify the incidence, bacterial patterns and predictors of device-associated NI, (ii) to identify the gap in KAP in infection control practices related to device-associated nosocomial infections, (iii) to develop and evaluate an intervention program and (iv) to develop a preliminary bed-side calculator to detect NI. This study was done in three phases.